Foreign language portfolio and EU funded foreign language courses in Poland - Kic-Drgas, Joanna; Sikora-Gaca, Małgorzata (Lingua Posnaniensis, 2018)
Due to globalization processes, the importance of the knowledge of foreign languages in almost every field of professional and private life is constantly growing. This has had an impact on the policy of many international institutions, including those in the European Union. Supporting language pluralism has been an explicit aim of the European strategy for multilingualism since 2008. The following paper presents the results of an interdisciplinary research study initiated by representatives of two different fields of science: linguistics and political science. Among the generation of young people aged between 18-24, who belong to the so-called Generation Z (White 2017: 224) and were brought up as EU citizens, the study points to a conflict between the perception of foreign language skills and opportunities to develop them using EU funds. The research aims to analyze the awareness of the EU language policy in Poland, combining questions related to people’s foreign language portfolio and knowledge about existing possibilities of learning foreign languages, as well as the ability to obtain external financing. The survey was conducted among 100 students of linguistic and non-linguistic studies and enabled the formulation of initial conclusions that are the basis for further research.